THE DIDACTIC VIEWS OF SCHOLAR ABU ABDULLAH KHOREZMI IN HIS CENTURIES - Nargiza Yunusalieva (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the didactic views of the scientist Abu Abdullah Khorezmi in his centuries have been presented, and at the same time, the scientist has taken a worthy place in the development of pedagogical thought by promoting the idea of human maturity and the importance of science in human relations. Khorezm’s major researches in the fields of mathematics, geography, geodesy, catastrophes were discussed.